Effect of Preconditioning by Light Load Eccentric Exercise Versus Heat on Markers of Muscle Damage in Collegiate Males - Zaheer, Sumbul (Asian J Sports Med, 2014)
BACKGROUND: Delayed onset muscle soreness (DOMS) occurs following unaccustomed or intense bouts of exercise. Previous research has demonstrated that that preconditioning with low load exercise or heat relieves muscle soreness. However, actively warming up the muscles with exercise may be an effective alternative. OBJECTIVES: This study compared preconditioning effect of light load eccentric exercise and heat using microwave diathermy on markers of muscle damage in collegiate males. PATIENTS AND METHODS: Thirty six sedentary collegiate males were randomly assigned into two experimental groups: 10% Eccentric exercise group (10% ECC group) and Microwave diathermy group (MWD group). Both the groups performed 30 repetitions of maximal eccentric exercise (Max-ECC) of the elbow flexors. The 10% ECC group performed light load eccentric exercise (10% ECC), five sets, six repetitions using a dumbbell set at 10% of maximal voluntary isometric contraction strength (MVC), 2 days prior to Max-ECC. The MWD group received heat using microwave diathermy (150 watts, 20 minutes) one day prior to Max-ECC. Changes in MVC, range of motion (ROM), upper arm circumference, soreness, were assessed before and 24-72 hours after whereas serum creatine kinase activity and lactate dehydrogenase (LDH) activity up to 48 hours following the Max-ECC were compared between groups by a mixed model ANOVA. RESULTS: No significant difference (P > 0.05) were found between the groups for changes in all variables post Max-ECC, except for LDH activity showing significant interaction effect (P = 0.04). CONCLUSIONS: Preconditioning with light load eccentric exercise and heat using microwave diathermy treatment did not differ in their effects on muscle damage markers after Max-ECC. However, with time their effects on LDH activity were found to be different.